Rancang Bangun Sistem Penghitungan Pencapaian Standar Pelayanan Minimal (SPM) Pendidikan Dasar dengan Algoritma Fuzzy Logic - Agunawan Agunawan; Paula Eka Wijaya (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
The quality of basic education is required by the district / city government by meeting the Minimum Service Standards (MSS) for Basic Education, namely the elementary / MI and junior high school / MTs levels consisting of 27 indicators based on Permendikbud No. 23 Tahun 2013. This research is to create a web-based application using the fuzzy logic algorithm of the Mamdani method (Min-Max) which will map and analyze SPM fulfillment gaps, policies taken and calculate fulfillment costs. Will be stated in a roadmap document for SPM fulfillment. Generated Basic Education SPM roadmap document is expected to be used as a reference by the district/city government in making policies and budgeting in order to fulfill MSS. Methodology using Research and Development (R&D), Fuzzy logic testing method using pivot table and black box test for web application.